Application of pH and TDS Sensors to Optimize the Growth of Pakcoy (Brassica rapa L.) Plants in Hydroponic Systems - Mardaniyah, Annisa; Fevria, Resti; Kardiman, Reki; Vauzia, Vauzia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pakcoy (Brassica rapa L.) is a widely cultivated leafy vegetable with high economic value. Limited agricultural land and the need for more efficient cultivation systems encourage the use of hydroponic technology, particularly through the use of pH and TDS sensors to optimize nutrient management. This study aims to compare the growth of pakcoy plants using the Deep Flow Technique (DFT) hydroponic system with pH and TDS sensors and without sensors. The study used a Completely Randomized Design (CRD) with two treatments: 50% AB mix + 50% POC with sensors, and 50% AB mix + 50% POC without sensors, with nine replications. The parameters observed included plant height, number of leaves, leaf area, fresh weight, and dry weight. Data were analyzed using an unpaired t-test at a significance level of 5%. The results showed that the use of pH and TDS sensors significantly affected all growth parameters. The treatment with sensors resulted in higher average values, namely plant height of 25.1 cm, number of leaves of 17.3, leaf area of 514.6 cm², fresh weight of 236.28 g, and dry weight of 30.7 g compared to the treatment without sensors. Automatic nutrient monitoring creates stable solution conditions, thereby increasing nutrient absorption efficiency and plant biomass accumulation. This study concluded that the use of pH and TDS sensors is effective in optimizing and increasing the productivity of bok choy plants in hydroponic systems. It is recommended that IoT-based monitoring technology be applied more widely to improve cultivation efficiency, reduce costs, and support sustainable agriculture.